50 wellbeing lessons for the diverse primary classroom : teaching through inclusive practice - Tailor, Manisha; Tailor, Radhika (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is designed to support teachers in promoting social and emotional wellbeing within their diverse classroom. With 50 detailed lessons plans and supplemented resources to promote discussion, each lesson plan contains learning outcomes, activity descriptions and further questions around areas of diversity specific to race, culture and LGBTQ . This accessible text offers a collection of activities with supplemented resources on a wide range of pertinent topics that challenge children to reflect, ask questions, analyse and find solutions through open discussion and collaboration. It provides them with the opportunity to explore their feelings and understand empathy and develop coping strategies in order to promote mental wellbeing. The content covered in this resource includes topics such as the psychological impact of discrimination, the Black Lives Matter movement, prejudice, coping with loss, feeling left out, moving school and managing as a young carer. A practical guide ideal for those new to teaching as well as more experienced practitioners, this resource will help address social and emotional wellbeing through themes that often effect marginalised groups and is crucial reading for anyone looking to embed an inclusive mental wellbeing culture within their school"--
What is mental health? -- My mindful mind -- Small and big feelings -- How would you feel? -- Emotional rollercoaster -- Keeping calm -- Raj and his love for football -- Helping Raj -- Is this a stranger danger type of thing? -- Cyberbullying -- Growth and fixed mindset -- Super strengths -- Goal setting -- Let's celebrate! -- Tree of growth -- Gratitude -- Implementing change -- Needs and wants -- What makes you happy? -- What makes a good friend? -- Making friends -- Managing decisions -- Samita and her mum -- Young carers -- Left out and forgotten -- Feeling left out -- Luciana and her grandma -- My special person -- Resilience toolbox -- Madam C.J. Walker -- Ali Jawad -- What is depression? -- Worrying -- Jasmine's fear of failure -- Exam pressure -- A new environment -- Life of a refugee -- Psychological impact of Islamophobia -- What is Black Lives Matter? -- Hope Powell : being first -- Lewis Latimer : inventor and pioneer -- My identity -- My mums are gay -- Disability discrimination -- Imagine my world.
OCLC-licensed vendor bibliographic record.
Keywords: School children -- Great Britain -- Psychology; School children -- Mental health -- Great Britain; Multicultural education -- Great Britain; Classroom environment -- Great Britain; Well-being.; EDUCATION / General; EDUCATION / Elementary